FORMULATION DEVELOPMENT AND EVALUATION OF CALCIPOTRIOL AND PREDNICARBATE FOR TOPICAL TREATMENT OF PSORIASIS - Phatangare, Jyoti (Journal of Drug Delivery and Therapeutics, 2014)
Calcipotriol and Prednicarbate are widely used effective treatments for psoriasis vulgaris. Combined therapy is known to be superior to monotherapy, but the drug substance degrades when mixed together. The purpose of the study was to develop a formulation which combines Calcipotriol and Prednicarbate in a single vehicle hereby with optimal drug delivery into the skin. As the two substances are incompatible in aqueous and alcoholic medias, different non-aqueous formulations were prepared with suitable solvents and antioxidants. Formulations based on DPPG had no overall effect on skin permeability. However, A 5% polyoxypropylene-15 stearyl ether (PSE) formulation had a marked effect, resulted in a permeation rate comparable to the marketed combination product Diavobet (Calcipotriol and Betamethasone ointment). Thus, by using PSE as solvent, it was possible to combine Calcipotriol and Prednicarbate in a single formulation. Â  Keywords: Calcipotriol, Prednicarbate, polyoxypropylene-15 stearyl ether, psoriasis vulgaris.